Survey on Improving System Security using BGP and IP Prefix Hijacking (International Journal of Engineering and Computer Science, 2015)
Border Gateway Protocol (BGP) is a standardized exterior gateway protocol designed to exchange routing andreachability information between autonomous systems (AS).The protocol is often classified as a path vector protocol but issometimes also classed as a distance vector routing protocol. The Border Gateway Protocol does not involve traditional InteriorGateway Protocol (IGP) metrics, but makes routing decisions based on path, network policies and/or rule-sets configured by anetwork administrator. The Border Gateway Protocol plays a key role in the overall operation of the Internet and is involved inmaking core routing decisions. The Border Gateway Protocol is the successor to the Exterior Gateway Protocol (EGP) and iscurrently the most widely used exterior gateway protocol by Internet service provider (ISP) due to the fact that BGP allows forfully decentralised routing.